Are polarized courts dangerous for litigation? Evidence from French labor courts. Issue 5 (11th October 2021) - Nizza, Umberto
Abstract: France relies on unionized judges to assess labor cases in court. The economic literature advocates that judges pertaining to the more belligerent unions alter judicial equilibrium, foster lower settlements, avoid trials, and intensify a professional judge's interventions. This paper intends to test whether such speculations are accurate. The empirical evidence provided here suggests that such fears are not grounded. Using a database on French employment courts, between 2012 and 2016, we show that judges from the most adversarial trade unions foster conciliation and reduce the number of dropped legal cases. The lack of statistically significant impact of unions on the judicial institution's dysfunctions is evident: the labor judiciary's alleged polarization does not drive the rate of appeals and the number of professional judges' intervention. Finally, the judicial malfunctions appear to be driven by institutional distortions and local socio-economic conditions.